2020
DOI: 10.3390/ani10030519
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Physicochemical Traits of Carcasses and Meat from Geese Fed with Lupin-Rich Feed

Abstract: The aim of the study was to analyze the quality of geese meat receiving feed with soybean meal (group 1), yellow lupin (group 2), narrow-leaved lupin (group 3), or white lupin (group 4). In total, 400 male White Kołuda® geese were randomly assigned to four groups, with 10 replicates and 10 birds each, during the 77-day rearing period. After the end of the rearing period, 10 birds from each group were slaughtered and dissected. Meat quality traits were measured. Based on the production results, it can be conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…40% of protein. However, new varieties of lupin created in breeding studies are characterised by much lower levels of antinutrients deteriorating growth performance in poultry 10 – 12 . Another alternative source of energy and protein is rapeseed meal (RSM) 7 , a by-product of rape processing 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40% of protein. However, new varieties of lupin created in breeding studies are characterised by much lower levels of antinutrients deteriorating growth performance in poultry 10 – 12 . Another alternative source of energy and protein is rapeseed meal (RSM) 7 , a by-product of rape processing 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Hang et al 13 concluded that the addition of vitamins to feed with a 5 or 10% inclusion of RSM can minimize the negative effects of antinutrients. Kuźniacka et al 12 compared the effects of diets containing different sources of protein on the quality of meat from ducks. The best quality parameters were found in ducks fed diets with 57.78–42.22% inclusions of yellow lupin and 17.87–34.49% inclusions of RSM in starter and grower feeds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Baéza et al [ 5 ] described the effect of preslaughter conditions on poultry meat pH in their review. Moreover, other authors who studied different goose feeding [ 6 ] explained the differences in pH of breast by slaughter process.…”
Section: Resultsmentioning
confidence: 99%
“…These traits also can determine the suitability of raw meat for further processing and influence the economic aspect of meat production [ 1 , 5 ]. Moreover, the quality of meat from broiler geese depends on the genotype, age of birds, and their management system, particularly the diet [ 6 , 7 ]. Geese as herbivorous poultry can utilize cheap feed resources and be reared in different systems [ 2 , 8 , 9 , 10 ]; however, concentrated ad libitum feeding is widely used [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation